Institutional Setting and Its Influence on the Teaching of Mathematics: Implications to Implementing Reform Vision in Mathematics Education in Ethiopian Schools - Dereje Taye Wondem; Solomon Abedom Tesfamicael; Dawit Asrat Getahun (MDPI AG, 2023)
Existing initiatives in mathematics education demand establishing a continuous professional development program for teachers in Ethiopian schools. However, implementing such programs first requires an understanding of the school and district environment in which the participating teachers work, as mathematics instruction is in part a function of the environment. In many cases, school and district settings are dynamic, and it is difficult to incorporate unplanned and intervening factors into the change process. This case study attempts to investigate the influences of the school and district settings in promoting reform visions in mathematics education. This study applies the theory of communities of practice as a framework and qualitative coding of data to understand the dynamic school setting and its implications for the teaching practices of mathematics teachers. The findings reveal that the school setting does not adequately promote reform visions, but rather it maintains the practice that is supposed to be changed. The current situation includes an accountability system loosely connected to reform visions, the absence of reform-oriented school leaders and expertise to guide the teachers, and a lack of instructional materials that the teachers can refer to regarding the new reforms. This paper suggests a possible configuration of the school situation to promote an environment that fosters the teaching of mathematics toward reform objectives.